A study on how Aarong develops and introduces new product and implements its plan (HERSTORY) - Sharry, Sajid Imtiaz (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.